Smoking cessation after acute coronary syndrome: A systematic review and meta‐analysis. Issue 12 (30th September 2021) - Lovatt, Saul; Wong, Chun Wai; Holroyd, Eric; Butler, Rob; Phan, Thanh; Patwala, Ashish; Loke, Yoon K.; Mallen, Christian D.; Kwok, Chun Shing
Abstract: Background: Smoking cessation is an effective secondary prevention measure after acute coronary syndrome (ACS). We conducted a systematic review with the aim to better understand which patients have a greater propensity to quit smoking and the risk factors for continued smoking after ACS. Methods: We searched MEDLINE and EMBASE for studies that evaluated smoking cessation after ACS. The pooled rate of smoking cessation across included studies was performed. Random effects meta‐analysis for different variables and their association with smoking cessation was conducted. Results: A total of 39 studies with 11 228 patients were included in this review. The pooled rate of smoking cessation following ACS across 38 studies was 45.0%. Factors associated with greater likelihood of smoking cessation were attendance at cardiac rehabilitation (OR 1.90 95% CI 1.44‐2.51), married/not alone (OR 1.68 95% CI 1.32‐2.13), intention/attempt to quit smoking (OR 1.27 95% CI 1.11‐1.46), diabetes mellitus (OR 1.24 95% CI 1.03‐1.51) and hospitalised duration (OR 1.09 95% CI 1.02‐1.15). Variables associated with a lower likelihood of smoking cessation were depression (OR 0.57 95% CI 0.43‐0.75), chronic obstructive pulmonary disease/lung disease (OR 0.73 95% CI 0.57‐0.93), previous admission with acute myocardial infarction/cardiac admission (OR 0.61 95% CI 0.47‐0.80), cerebrovascular disease/transient ischaemic attack (OR 0.42 95% CI 0.30‐0.58) and unemployment (OR 0.37 95% CI 0.17‐0.80). Conclusions: The majority of smokers with an ACS continue to smoke after admission. Patients attending cardiac rehabilitation show increased odds of quitting while people who are depressed and those with chronic lung disease were less likely to quit smoking and should be targeted for intensive smoking cessation interventions.